2000
DOI: 10.1007/bf02360540
|View full text |Cite
|
Sign up to set email alerts
|

Is dormancy breaking of potato tubers the reverse of tuber initiation?

Abstract: SummaryTuber formation is a well orchestrated physiological event that involves many metabolic changes. Dormancy gradually develops in potato tubers from the moment cell division in the stolon tip has stopped and the tuber starts to develop. Dormancy breakage may be the reverse of dormancy initiation suggesting that there may be similarities between tuber induction and dormancy development.Based on a literature review it is concluded that, when comparing tuber induction and the breaking of dormancy, hormonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 70 publications
5
49
0
2
Order By: Relevance
“…Since tuber dormancy is established during tuber formation, it is not surprising that factors influencing tuberisation such as day length, temperature, nutrient and water supply also affect dormancy and sprouting (summarised in Jackson 1999; Claassens and Vreugdenhil 2000;Suttle 2007). Early work reported that potatoes cultivated under short days have a shorter dormancy period than those grown under long-day conditions (Emilsson 1949; reviewed by Claassens and Vreugdenhil 2000). Besides day length, temperature has a strong impact on tuber development.…”
Section: Environmental Conditions Affecting Length Of Tuber Dormancymentioning
confidence: 99%
See 2 more Smart Citations
“…Since tuber dormancy is established during tuber formation, it is not surprising that factors influencing tuberisation such as day length, temperature, nutrient and water supply also affect dormancy and sprouting (summarised in Jackson 1999; Claassens and Vreugdenhil 2000;Suttle 2007). Early work reported that potatoes cultivated under short days have a shorter dormancy period than those grown under long-day conditions (Emilsson 1949; reviewed by Claassens and Vreugdenhil 2000). Besides day length, temperature has a strong impact on tuber development.…”
Section: Environmental Conditions Affecting Length Of Tuber Dormancymentioning
confidence: 99%
“…Other post-harvest conditions such as humidity and the composition of the atmosphere also impair dormancy (see Wiltshire and Cobb 1996;Claassens and Vreugdenhil 2000;Suttle 2007). …”
Section: Environmental Conditions Affecting Length Of Tuber Dormancymentioning
confidence: 99%
See 1 more Smart Citation
“…Asterisk denotes values significantly different from the wild type control lower in the phosphoglucomutase overexpressing lines. Whilst a major role in the breaking of dormancy is clearly played by hormones with evidence being presented for the involvement of gibberellins (Carrera et al 2000), abscisic acid (Claassens and Vreugdenhil 2000), cytokinins (Galis et al 1995) and ethylene (Claassens and Vreugdenhil 2000), evidence is beginning to accumulate for a parallel role of carbohydrate metabolism. The most compelling, albeit surprising, result was observed when analysing transgenic plants ectopically expressing a bacterial pyrophosophatase.…”
Section: Effect Of E Coli Phosphoglucomutase Expression On Heterotromentioning
confidence: 99%
“…The fact that single applications of GA 3 increase vegetative growth without essentially affecting yield indicates that the inhibitory effects of GA 3 on tuberisation relate to temporary changes in enzymes involved in carbohydrate metabolism. 17 On the other hand, the reduction in mean tuber yield following repeated applications of GA 3 (Table 6) apparently relates not only to a reduction in photosynthesis resulting from the lower chlorophyll content of leaves (Table 5) but also to the increased utilisation of sugars for vegetative growth at the expense of starch accumulation in the tubers, 8 thus increasing the dry matter content of the shoots but decreasing that of the tubers. 18 However, other mechanisms may also be involved, since GA 3 application has also been reported to inhibit adenosine-5-diphosphoglucose pyrophosphorylase (AGP-ase) activity in developing tubers, with a concomitant reduction in starch accumulation.…”
Section: Resultsmentioning
confidence: 99%